2019
DOI: 10.3390/atmos10050280
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Air-Mass Trajectories and the Abundance of Dust-Borne Prokaryotes at the SE Mediterranean Sea

Abstract: Airborne prokaryotes are transported along with dust/aerosols, yet very little attention is given to their temporal variability above the oceans and the factors that govern their abundance. We analyzed the abundance of autotrophic (cyanobacteria) and heterotopic airborne microbes in 34 sampling events between 2015–2018 at a coastal site in the SE Mediterranean Sea. We show that airborne autotrophic (0.2–7.6 cells × 103 m−3) and heterotrophic (0.2–30.6 cells × 103 m−3) abundances were affected by the origin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…Bacterial abundances in aerosols collected over the MS were in agreement with previous studies from the eastern Mediterranean coast [10] and the Atlantic, Pacific, and Indian ocean basins [1], yet were lower than those reported in the East China Sea [54] and the Red Sea [55]. Rahav et al [10] measured the abundance of airborne prokaryotes at a coastal site located at the easternmost MS during 34 sampling events (between 2015 and 2018) and found that abundances were positively correlated to the concentration of aerosols in the air (mg m −3 air). Here, however, we did not find such a correlation, likely because the range of concentrations during non-dust-storm conditions, represented by our samples, was relatively small in comparison to previous studies.…”
Section: Airborne Bacterial Abundancesupporting
confidence: 90%
See 3 more Smart Citations
“…Bacterial abundances in aerosols collected over the MS were in agreement with previous studies from the eastern Mediterranean coast [10] and the Atlantic, Pacific, and Indian ocean basins [1], yet were lower than those reported in the East China Sea [54] and the Red Sea [55]. Rahav et al [10] measured the abundance of airborne prokaryotes at a coastal site located at the easternmost MS during 34 sampling events (between 2015 and 2018) and found that abundances were positively correlated to the concentration of aerosols in the air (mg m −3 air). Here, however, we did not find such a correlation, likely because the range of concentrations during non-dust-storm conditions, represented by our samples, was relatively small in comparison to previous studies.…”
Section: Airborne Bacterial Abundancesupporting
confidence: 90%
“…To our knowledge, there are only two other studies of airborne microbes in the MS during non-storm conditions [10,32]. The study site of Gat et al [32] was done at a coastal city in Israel (~10 Km away from the shoreline) and the study site of Rahav et al [10] was at the rooftop of a building directly next to the ocean. Thus, these studies represent different ecological systems than the open ocean.…”
Section: Airborne Microbiome Above the Msmentioning
confidence: 99%
See 2 more Smart Citations
“…Actinobacteria abundance was also significantly higher in the Atlantic AMBL compared to the water (t-test, p-value < 0.0001). Airborne Actinobacteria and Firmicutes have been previously connected to desert dust samples in the Eastern Mediterranean (23)(24)(25), and detected in different studies of airborne bacteria (26)(27)(28). In addition, Firmicutes are usually more abundant in soils than in marine surface water (2,21).…”
Section: Regional Distribution Of Airborne and Surface Water Bacterial Phyla In Thementioning
confidence: 99%